Electromagnetic interference shielding using ITO nano-branch and metal nano-particle decoration - Kim, Youngho; Yu, Hak Ki (Proceedings of the International Display Workshops, 2019)
The ITO branches were used for transparent and flexible electromagnetic interference shielding devices. Nano branch structure is expected to increase EMI shielding efficiency through inter-reflection with each branch. In order to increase the electromagnetic absorption rate of the ITO branch, novel metal nanodot is decorated. The application method to the transparent substrate is transfer using NaCl as sacrificial layer.
Keywords: Absorption rates; Branch structure; Electromagnetic interference shielding; EMI shielding; Flexble; Inter-reflection; Metal nano-particles; Shielding devices; Shielding efficiency; Transparent; EMI shielding; Flexble; Transparent